Assessment of fluid responsiveness as a component of hemodynamic monitoring in the operating room and intensive care unit - N.V. Matolinets; I.I. Yakymenko (Медицина неотложных состояний)
Fluid therapy is a critical, and often primary treatment modality in the management of various critical conditions. Like any therapeutic intervention, intravenous fluids require precise indications, contraindications, and dosing, all determined through the assessment of a patient’s volume status. Hemodynamic assessment plays a pivotal role in the treatment of critically ill patients, enabling clinicians to administer appropriate fluid therapy and cardiovascular support to optimize tissue perfusion and oxygenation. Traditional methods of assessing fluid responsiveness, which are predominantly static such as central venous pressure and pulmonary artery occlusion pressure, often fall short in their predictive accuracy under dynamic clinical conditions. Consequently, there is a growing interest in dynamic methods of fluid responsiveness assessment, which analyze cardiovascular response to specific preload changes. This literature review aims to explore various dynamic methods of hemodynamic assessment, discussing their advantages and limitations based on sources from databases like PubMed and MEDLINE.